Apoyo familiar percibido por usuarios/as en tratamiento de diálisis peritoneal ambulatoria continua del hospital victor lazarte echegaray - essalud. trujillo, año 2015 - Soriano Bohytron, Cinthya Lorena (2016)
This research is aimed to identify prevalent types of family support which have been perceived by users in Peritoneal Dialysis Continuous Ambulatory treatment (PDCA) of the Hospital “Victor Lazarte Echegaray”. A descriptive study about family support, based on the collection of data to identify and define the characteristics of the types of perceived family support for the 57 members of PDCA receiving treatment, was performed. At the same time, techniques of observation, structured and unstructured interview, questionnaires, records observations and interviews were used for the data collection, as instruments. The reliability of the instrument was achieved by selecting a pilot sample selecting the analysis unit which has similar characteristics to the study sample. As results, we get that the familiar type of prevalent support in users in PDCA treatment is the informational support, represented by 81.4%, which was characterized by strengthening recommendations by health team members of the family. The second type of prevalent support was emotional support, where the prevailing feature of emotional support, represented by the 89.5%, was the emotional intervention that the family does so that the users feel better in moments of depression, and finally the instrumental support, where the main feature which was represented by 98.2% was the direct help to comply the recommendations given by the health team, This help relates to the treatment process which must be practiced in their homes without forgetting the care of food and medication.